Development of the aeromagnetic space debris deorbiting system - Lapkhanov, Erik; Khoroshylov, Serhii (Eastern-European Journal of Enterprise Technologies, 2019)
The study has considered the possibility of creating an aeromagnetic system for removing space debris from low Earth orbits. The peculiarity of the design of the aeromagnetic deorbiting system is the use of magnetic controls for the relative position of the aerodynamic element with permanent rotary magnets that are shielded with the help of special screen capsules with shutters. It should be noted that this system is offered for aerodynamically unstable spacecraft. Besides, to analyse the performance and benefits of using permanent magnet aeromagnetic input systems, a corresponding discrete law is proposed to control the magnetic parts. The control of the relative position of the aerodynamic element in the orbital coordinate system is carried out in order to orient and stabilize it perpendicular to the dynamic incident atmospheric flow. A mathematical simulation has been performed for the orbital motion of a spacecraft during its removal with the help of a permanent magnet aeromagnetic system from different orbits. It has been determined that when stabilizing the aerodynamic element perpendicular to the vector of the incident dynamic atmospheric flow, the withdrawal time is reduced by 25 % compared with the non-oriented passive deorbiting. However, this advantage during the removal time is peculiar only to aerodynamic elements whose midsection area is much larger than a quarter of the total surface area. It is noteworthy that the design of aeromagnetic evacuation systems is only appropriate using aerodynamically deployable sail elements and is not effective at all for large inflatable elements. Thus, the development of an aeromagnetic space debris removal system with permanent magnet controls extends the boundaries of effective use of aerodynamic sailing systems. The use of permanent magnet units provides a new direction for further research on the orientation of large-scale space systems with minimal fuel and onboard energy consumption